Probiotics: an effective feed supplemnt in Shrimp culture (Journal of Bangladesh Academy of Sciences, 2014)
The application of antibiotics are of no use, because of its ineffectiveness in many cases, or result in increases in virulence of pathogens and, furthermore, are cause for concern in promoting transfer of antibiotic resistance to human pathogens. As a remedial measure, application of gut/ intestinal probiotics as a supplement along with feed has been suggested for shrimp culture as an effective farming practice for better growth, FCR (Feed conversion ratio) and disease control. The effect of gut probiotics mixed in a feed was studied for its effect on black tiger shrimp Penaeus monodon) in the Aquaculture Department Laboratory of College of Marine Science and Technology, Massawa, Eritrea- (Northeast Africa) and was found to be effective in providing higher growth, better FCR and resistant to pathogenic infections. DOI: http://dx.doi.org/10.3329/jbas.v38i2.21336 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 2, 127-130, 2014